The Emerging World of Membrane Vesicles: Functional Relevance, Theranostic Avenues and Tools for Investigating Membrane Function - Srivatsav, Aswin T.; Kapoor, Shobhna (Frontiers in Molecular Biosciences, 2021)
Lipids are essential components of cell membranes and govern various membrane functions. Lipid organization within membrane plane dictates recruitment of specific proteins and lipids into distinct nanoclusters that initiate cellular signaling while modulating protein and lipid functions. In addition, one of the most versatile function of lipids is the formation of diverse lipid membrane vesicles for regulating various cellular processes including intracellular trafficking of molecular cargo. In this review, we focus on the various kinds of membrane vesicles in eukaryotes and bacteria, their biogenesis, and their multifaceted functional roles in cellular communication, host-pathogen interactions and biotechnological applications. We elaborate on how their distinct lipid composition of membrane vesicles compared to parent cells enables early and non-invasive diagnosis of cancer and tuberculosis, while inspiring vaccine development and drug delivery platforms. Finally, we discuss the use of membrane vesicles as excellent tools for investigating membrane lateral organization and protein sorting, which is otherwise challenging but extremely crucial for normal cellular functioning. We present current limitations in this field and how the same could be addressed to propel a fundamental and technology-oriented future for extracellular membrane vesicles.